2020
DOI: 10.3390/brainsci10080565
|View full text |Cite
|
Sign up to set email alerts
|

Thiamine Deficiency Causes Long-Lasting Neurobehavioral Deficits in Mice

Abstract: Thiamine deficiency (TD) has detrimental effects on brain health and neurobehavioral development, and it is associated with many aging-related neurological disorders. To facilitate TD-related neuropsychological studies, we generated a TD mouse model by feeding a thiamine-deficient diet for 30 days, followed by re-feeding the control diet for either one week or 16 weeks as recovery treatment. We then performed neurobehavioral tests in these two cohorts: cohort of one week post TD treatment (1 wk-PTDT) and 16 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 76 publications
0
3
2
Order By: Relevance
“…This study reveals that vitamin B1 levels partially show no significant effect on anxiety symptoms, contradicting previous research (23,24,27). Previous research has indicated that vitamin B1 deficiency can decrease GABA levels and disrupt serotonin levels in the brain, leading to anxiety symptoms in experimental animals (22,23).…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…This study reveals that vitamin B1 levels partially show no significant effect on anxiety symptoms, contradicting previous research (23,24,27). Previous research has indicated that vitamin B1 deficiency can decrease GABA levels and disrupt serotonin levels in the brain, leading to anxiety symptoms in experimental animals (22,23).…”
Section: Resultscontrasting
confidence: 99%
“…This study reveals that vitamin B1 levels partially show no significant effect on anxiety symptoms, contradicting previous research (23,24,27). Previous research has indicated that vitamin B1 deficiency can decrease GABA levels and disrupt serotonin levels in the brain, leading to anxiety symptoms in experimental animals (22,23). The disparity between previous research and this study lies in the research subject, where previous studies used rats as experimental animals, whereas this study involved humans as research subjects.…”
Section: Resultscontrasting
confidence: 99%
“…Thiamine deficiency (TD) has long been associated with alcoholism ( Leevy and Baker, 1968 ; Woodhill and Nobile, 1972 ; Butterworth, 1995 ) and has been implicated as a key factor for alcohol-induced brain damages ( Martin et al, 2003 ; Liu et al, 2017 ). Our recent publication indicated thiamine deficiency can cause anxiety-like behaviors ( Li et al, 2020 ). Xu et al showed chronic voluntary alcohol drinking caused a significant decrease in the levels of thiamine in the brain but not the blood of male cHAP mice ( Xu et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, thiamine is a water-soluble vitamin that plays an important role in the biological processes such as glucose metabolism ( Polegato et al, 2019 ). There is evidence showing that the deficiency of the thiamine led to long-term neurobehavioral deficits, such as anxiety disorders ( Li et al, 2020 ). In fact, thiamine supplementation can prevent the occurrence of anxietious behaviors ( Markova et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%